2021
DOI: 10.1177/15353702211009787
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Th1/Th2 and Th17/Treg by pDC/mDC imbalance in primary immune thrombocytopenia

Abstract: This study investigates the regulatory effect of plasmacytoid dendritic cells (pDC)/myeloid dendritic cells (mDC) imbalance on balance of Th1/Th2 and Th17/Treg in primary immune thrombocytopenia (ITP). A total of 30 untreated ITP patients and 20 healthy controls were recruited. Compared with healthy control, the pDC proportion of ITP patients was significantly reduced ( P = 0.004), while the mDC proportion was not significantly changed ( P = 0.681), resulting in a decrease in the pDC/mDC ratio ( P = 0.001). Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…ITP was thought to occur primarily due to antibody-mediated autoimmune diseases. Current studies 1 , 2 have reported that cellular immunity also plays a role in the pathogenesis of ITP. T cells especially play an important role in pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…ITP was thought to occur primarily due to antibody-mediated autoimmune diseases. Current studies 1 , 2 have reported that cellular immunity also plays a role in the pathogenesis of ITP. T cells especially play an important role in pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines, which include Th17, Th1, and Th2, are key chemicals in the immunological and neurological systems. They can coordinate this migration of T and B cells to inflammatory areas, promote T cell activity and help B cell activation, and play a role in regulating immunity-inflammation in the immune system [ 66 ]. Following psychological stress, activated T cells can enter the central nervous system in a variety of ways, reduce inflammation, and support neuronal integrity via cellular immunity, thus modifying depressed behavior [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a series of findings suggest that lymphocyte levels were closely associated with the development and progression of primary immune thrombocytopenia. This may be due to the fact that (1) lymphocytes are a type of leukocyte, produced mainly by lymphoid organs, are an important cellular component of the body's immune response function, and are the main performers of the immune function [ 9 , 10 ]. In terms of physiology, but in the presence of pathogenic microorganisms, cancer cells, and allogeneic cells in the human body, lymphatic T cells and B cells were transformed and differentiated into allergenic T lymphocytes, plasma cells, and immunoglobulins to remove the invading substances, participate in humoral immunity and reduce the degree of damage to the organism, while NK cells have the role of killing target cells and are important in promoting the recovery of the inflammatory response and maintaining the health of the organism [ 11 ].…”
Section: Discussionmentioning
confidence: 99%